Technology Integration in Mathematics Classrooms: Impact, Challenges and Solutions Introduction - Brown, Esther (Jurnal Inovasi Pembelajaran Matematika, 2022)
Mathematics education has always been a crucial aspect promoted by the Jamaican government, wherein teachers serve as one of the main sources in imparting this knowledge to students. However, since the pandemic, drastic changes in the educational system have forced teachers, if not all, to adapt to this shift. This essay discusses the need for technology integration in mathematics classroom learning, emphasizing the importance of knowledge and skills that teachers must possess to effectively integrate technology. Additionally, the essay highlights the positive impact of technology integration on students' learning in mathematical concepts. However, there are challenges faced by teachers, such as lack of digital skills and access to resources. Solutions to address these challenges are also discussed, including effective training, technical support, and increased access to devices and technological resources. Thus, the essay underscores the importance of technology integration in mathematics education and the efforts required to overcome associated challenges.